Community awareness in solid waste generation at Bandar Baru Bangi-Selangor Darul Ehsan / Hendri Yani and Jamaluddin Md. Jahi - Yani, Hendri; Md. Jahi, Jamaluddin (2004)
Economic establishment and modernization has its share of disadvantages and one of the main aspects of concern is the pollution it is causing to the earth-be it land, air, and water. Due to the increase in the global population and the rising demand for food and other essentials, there has been a rise in the amount of waste being generated daily by each household. This waste is ultimately thrown into municipal waste collection centres from where it is collected by the area municipalities to be further thrown into the landfills and dumps. However, either due to resource crunch or inefficient infrastructure, not all of this waste gets collected and transported to the final dumpsites. If at this stage, the management and disposal is improperly done, it can cause serious impacts on health and problems to the surrounding environment. In order to avoid the problems caused by the increasing amount of solid waste generated everyday, the Government of Malaysia through the Ministry of Housing and Local Government launched the practice of integrated solid waste management program, where the first step is the source reduction or reduce the generation followed by the resources recovery through the recycling and disposal of the residuals safely to the sanitary landfills. The objective of this paper is to identify the awareness of the communities in solid waste generation at Bandar Baru Bangi town. In order to achieve the objective, a survey has been conducted over the communities in the study area. The results showed that most. of the community members have awareness on the solid waste generation issue and almost 80% communities have awareness on the types of solid waste they generate. Most of the community members think before buy their household materials, which normally generate solid waste.